PSYCHOLOGICAL CHARACTERISTICS OF ANGER OBSERVED IN TEENAGERS - Ezoza Mannabova; Shoira Dusmukhamedova (American Journals Publishing, 2022)
Anger is a normal, common human emotion. It cannot be evaluated as good or bad. Anger tells a person that a situation is hurtful, unfair, or threatening. While it is perfectly normal to feel angry when people are mistreated or insulted, anger becomes a problem when it is expressed in ways that hurt ourselves or others.You might think it’s normal for us to vent our anger. But the truth is that anger can affect the way people treat us. This can have a negative impact on the way of life of teenagers who have started to join the ranks of adults, and can hinder the way to success.
Keywords: Anger, psychological trait, teenager, amygdala, prefrontal cortex , personality